2017
DOI: 10.1017/s1047951117001706
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the concept of oxygen transport in the critically ill, with a focus on children after cardiopulmonary bypass

Abstract: The concept of oxygen transport, defined as the relation between oxygen consumption (VO2) and delivery (DO2), is of fundamental importance in critically ill patients. The past 200 years have witnessed a stepwise progressive improvement in the understanding of pathophysiological disturbances in the balance of DO2 and VO2 in critically ill patients including those after cardiopulmonary bypass surgery. Intermittent spectacular technological achievements have accelerated the rate of progress. Therapeutic advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Similarly, previous studies have found that the retinal vascular morphology, such as dilatation and tortuosity, would return to normal after cardiac surgery in CCHD patients ( 21 , 22 ). On the one hand, postoperative higher oxy-hemoglobin concentrations could enhance oxygen delivery to microcirculation ( 23 , 24 ). On the other hand, reduced blood viscosity could change the shear stress and increase nitric oxide (NO) production and result in vascular smooth muscle cell relaxation and vasodilation after surgery ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous studies have found that the retinal vascular morphology, such as dilatation and tortuosity, would return to normal after cardiac surgery in CCHD patients ( 21 , 22 ). On the one hand, postoperative higher oxy-hemoglobin concentrations could enhance oxygen delivery to microcirculation ( 23 , 24 ). On the other hand, reduced blood viscosity could change the shear stress and increase nitric oxide (NO) production and result in vascular smooth muscle cell relaxation and vasodilation after surgery ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…13,24 However, in our extensive experience, with certain meticulousness, accurate measurements can be achieved. 25 To date, only 4 studies compared measured REE and energy intake in post-CPB children. 2,20,26,27 The mean energy intake ranged from 3 to 16 kcal/kg/d, which accounted for 8%-22% of REE in the first 24 hours after CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect calorimetry is widely considered as difficult and even impossible, particularly in infants 13,24 . However, in our extensive experience, with certain meticulousness, accurate measurements can be achieved 25 . To date, only 4 studies compared measured REE and energy intake in post‐CPB children 2,20,26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Combined with arterial and venous blood gases, it is able to derive almost all elements of hemodynamics in varied circulations (5)(6)(7)9). However, it is technically and timely highly demanding and hardly used outside of clinical research settings (8).…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention of the Fick principle in 1870 ( 3 ), there have been intermittent technological developments to measure cardiac output, namely, Swan-Ganz catheter and thermodilution method in the 1970's ( 4 ), respiratory mass spectrometer in the 1990's ( 5 7 ). Thermodilution has well-known limitations when applied to post-CPB children ( 8 ). The presence of intracardiac shunt and tricuspid and pulmonary regurgitation can significantly affect its accuracy.…”
Section: Introductionmentioning
confidence: 99%